CODE MIXING ANALYSIS OF @SKIPBERAT X-ACCOUNTS' TWEETS - Zahro', Naura Izza; Nafihima, Fika Ar-Rizqi (Faculty of Teacher Training and Education, English Department, UNISKA, Kediri, 2024)
Numerous studies in the field of discourse analysis (DA) have utilized X application as their primary data source. This study examines code-mixing in tweets from the '@skipberat' Xaccount between May 18, 2024, and June 18, 2024. Using descriptive qualitative with focus on discourseanalysis, it explores the types of code mixing used by the X user ‘@skipberat’ in his tweets. The research identifiesand categorized the tweets into three types of code mixing namely insertion,alternation, and congruent lexicalization. Findings highlight that insertion emerging as the most frequent form followed by alternation and congruent lexicalization.Insertion code-mixing occurs when the speakers insert lexical items into another language.The example from the ‘@skipberat’ tweet is‘Panjang umur aespa karir kalian bakal longlasting’. The English word ‘long lasting’ is inserted in the last and it does not change the grammatical so it is categorized into insertion code mixing. There is still a lot of tweets can be analysedby code mixing or others issues in Discourse Analysis so the next researcher can explore more.